Agronomic and qualitative traits of common bean as a function of the straw and nitrogen fertilization1 - Flôres, Jordana De Araujo (2017)
ABSTRACT The no-tillage system can change the nitrogen dynamics in the soil, being necessary to adjust the nitrogen fertilization in order to provide this nutrient during critical phases of the common bean growth. This study aimed at evaluating the agronomic and qualitative traits of common bean grown under different straw types, as a function of the topdressing nitrogen fertilization splitting. A randomized block experimental design, in a split-plot arrangement, with four replications, was used. The plots consisted of three straw types (maize, maize intercropped with brachiaria and brachiaria), while the subplots comprised the combination of these straw materials with 8 topdressing nitrogen fertilization splitting arrangements. The common bean on brachiaria straw shows higher grain yields and crude protein contents. The nitrogen fertilization splitting, as topdressing, interacts with the straw types, increasing the number of pods per plant. The common bean plants growing on plots with single-maize straw had a shorter time for maximum hydration. The topdressing nitrogen fertilization splitting has no effect on the common bean qualitative traits.